MAKNA ṬĀGHŪT DALAM AL-QUR’AN: ANALISIS SEMANTIK - Mufidah Muhaimin; Muhammad Asif (STAI AL-ANWAR SARANG, 2017)
The Qur'anic tÄghÅ«t is one of the most often misused religious concept for supporting radicalism. Under the rules of Isutzuâ€™s scholarship, this research wants to approach the Qurâ€™anic tÄghÅ«t semantically. It concludes that the basic meaning for tÄghÅ«t in the Qurâ€™an is â€œtransgressing boundsâ€ whereas its relational meanings are: idols (in Q. 4: 61, 40: 17, 16: 36), propagandists of digression (Q. 2: 256, 257), false legislation attributed not to God and His Messenger (Q. 4: 60), polytheism (Q. 4: 76) and rebellion to God (Q. 5: 60).